2010
DOI: 10.1002/ajpa.21367
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication: Ectocranial suture closure in Pongo: Pattern and phylogeny

Abstract: Ectocranial suture fusion patterns have been shown to contain biological and phylogenetic information. Previously the patterns of Homo, Pan, and Gorilla have been described. These data reflect the phylogenetic relationships among these species. In this study, we applied similar methodology to Pongo to determine the suture synostosis progression of this genus, and to allow comparison to previously reported data on other large-bodied hominoids. We hypothesized these data would strengthen the argument that suture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
(61 reference statements)
1
12
0
Order By: Relevance
“…In addition, all scales exhibited strong reproducibility statistics suggesting homogeneity. Overall, the lateral‐anterior patterns of suture fusion were most homogenous, compared with the vault suture patterns within the Aleutian populations, similar to standards reported for Homo sapiens (Meindl and Lovejoy, 1985), and other Hominoids (Cray et al, 2008, 2010). The suture synostosis patterns reported here, although similar, differ slightly compared with standards reported in the literature (Meindl and Lovejoy, 1985).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, all scales exhibited strong reproducibility statistics suggesting homogeneity. Overall, the lateral‐anterior patterns of suture fusion were most homogenous, compared with the vault suture patterns within the Aleutian populations, similar to standards reported for Homo sapiens (Meindl and Lovejoy, 1985), and other Hominoids (Cray et al, 2008, 2010). The suture synostosis patterns reported here, although similar, differ slightly compared with standards reported in the literature (Meindl and Lovejoy, 1985).…”
Section: Discussionsupporting
confidence: 81%
“…Guttman scaling was used to determine the most commonly occurring patterns of ectocranial suture synostosis for commencement and termination, for those remains identified as Aleut, Paleo‐Aleut, and the collection combined. These results were compared with published standards for Homo sapiens ectocranial suture fusion progression (Table 2 ) (Meindl and Lovejoy, 1985; Cray et al, 2008, 2010). The Guttman approach assesses the likelihood of unidimensionality, a notion best assessed by the summary measure, CR, the coefficient of reproducibility.…”
Section: Methodsmentioning
confidence: 99%
“…At day 7, there were longer and bigger finger-like bones formed on the nasal side of expanded sutures compared with the oral side. This phenomenon may help to explain that the sutures have different timing of closure [3134], which is referred to as the “zipper” mechanism of sutural closure where fusing occurred first on one side of the suture [35]. Why there were more new finger-like bones forming on the nasal section of suture than the oral section is open to question.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on cranial suture biology has suggested there is biological and taxonomic information to be garnered from the heritable pattern of suture synostosis (Falk et al, ; Wang et al, ,; Cray et al, , , ; Wilson and Sanchez‐Villagra, ). Along with brain growth patterns, diet, and biomechanical forces, suture synostosis can influence phenotypic variability in cranial vault morphology (Moss and Young, ; Moss, ; Moss and Salentijn, ; Enlow and Hans, ; Herring and Teng, ; Mao, ; Fong et al, ; Byron et al, , ; Alaqeel et al, ; Byron, , ; Sardi et al, ; Herring, ; Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Along with brain growth patterns, diet, and biomechanical forces, suture synostosis can influence phenotypic variability in cranial vault morphology (Moss and Young, ; Moss, ; Moss and Salentijn, ; Enlow and Hans, ; Herring and Teng, ; Mao, ; Fong et al, ; Byron et al, , ; Alaqeel et al, ; Byron, , ; Sardi et al, ; Herring, ; Yu et al, ). Investigations concerning calvarial suture fusion have rarely concentrated on a phylogenetic perspective, with notable exceptions (Krogman, ; Chopra, ; Dolan, ; Brunner et al, ; Cray et al, , ; Bärmann and Sánchez‐Villagra, ; Flores and Barone, ; Goswami et al, ). This research has suggested intraspecies homogeneity in patterns, both for timing of suture fusion as well as general architectural pattern by which it occurs (Krogman, ; Chopra, ; Wang et al, ; Cray et al, , , ).…”
Section: Introductionmentioning
confidence: 99%